MEKANISME LETTER OF CREDIT SYARIAH DI PT BANK BNI SYARIAH - Yutika, Meisa; Sa'diyah, Diah Siti (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2018)
The existence of the changing times, demanding a State of international relations in order to support economic development. One form of international relations, namely business and international trade. one of the first in the international payment system is to use a letter of credit (LC) on the banking service product. LC Sharia is a product that is adopted from Conventional Banking products. However, until now, has not found the regulation governing implementation mechanisms explicitly Sharia LC in Indonesia. Therefore, the need for research on the mechanism of LC in the Islamic Penbankan In Indonesia. The purpose of this research was: 1) To compare the mechanism of implementation of the LC in Islamic banks and Conventional Banks, as well as looking for the difference between the two; 2) To know the regulations used in regulating Islamic Bank Sharia LC; 3) Mechanism to find out the views of the economic law of the Sharia (HES) against Sharia in LC mechanism Islamic banking in Indonesia.Â Â The framework of thought from this research that is using rule jurisprudence mu'amalah